2007
DOI: 10.1038/sj.jcbfm.9600451
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling Identifies the CRH/CRH-R1 System as a Modulator of Neurovascular Gene Activity

Abstract: Corticotropin-releasing hormone receptor type 1 (CRH-R1)-deficient mice display reduced anxietylike behavior, a chronic corticosterone deficit, and an impaired neuroendocrine stress response caused by disruption of the hypothalamic-pituitary-adrenocortical (HPA) axis. The molecular substrates and pathways of CRH/CRH-R1-dependent signaling mechanisms underlying the behavioral phenotype as well as the consequences of lifelong glucocorticoid deficit remain largely obscure. To dissect involved neuronal circuitries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Gene expression studies in inbred animal strains can identify gene expression changes in a homogeneous genetic background, with the signal not masked by the noise generated from the variable genetic background present in human studies [22•]. Furthermore, several inducible gene expression systems have been developed in transgenic animals that allow expression of certain genes of interest in distinct brain regions to be turned on and off [23]. These animals represent powerful tools that enable detailed studies of the impact of individual genes on gene expression.…”
Section: Choice Of Target Tissues For Gene Expression Studiesmentioning
confidence: 99%
“…Gene expression studies in inbred animal strains can identify gene expression changes in a homogeneous genetic background, with the signal not masked by the noise generated from the variable genetic background present in human studies [22•]. Furthermore, several inducible gene expression systems have been developed in transgenic animals that allow expression of certain genes of interest in distinct brain regions to be turned on and off [23]. These animals represent powerful tools that enable detailed studies of the impact of individual genes on gene expression.…”
Section: Choice Of Target Tissues For Gene Expression Studiesmentioning
confidence: 99%
“…GWAS studies have repeatedly shown that polymorphisms related to ␤-cell function and/or development are closely associated with type 2 diabetes (16,17), reviewed in (18). For this study, the acute insulin response to glucose (AIRg) test from the GUARDIAN Consortium was used as an indicator of islet function to evaluate genes from the rodent microarray (13).…”
mentioning
confidence: 99%
“…All sections were processed for in situ hybridization as previously described (Deussing et al, 2007). The riboprobe for UCN3 covered nucleotides 505-1136 of GenBank accession number NM_031250 and was generated by PCR, labeled, and hybridized as previously described (Deussing et al, 2007). The hybridized slides were dipped in autoradiographic emulsion (type NTB2; Eastman Kodak), developed after 3-6 weeks, and counterstained with cresyl violet.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure allowed for parallel in situ hybridization of sections under identical conditions assuring meaningful quantification and comparison of hybridization signals. All sections were processed for in situ hybridization as previously described (Deussing et al, 2007). The riboprobe for UCN3 covered nucleotides 505-1136 of GenBank accession number NM_031250 and was generated by PCR, labeled, and hybridized as previously described (Deussing et al, 2007).…”
Section: Introductionmentioning
confidence: 99%